PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR KECAMATAN SARONGGI KABUPATEN SUMENEP - jurnalmap map; Budiyono ÔÇì; Indra Prasetyo; Chamariyah ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT The purpose of this study is 1) To know and test how the description about leadership style, organizational culture, motivation and work performance of employees, 2) To know and test whether leadership style, organizational culture and motivation influence simultaneously to the performance of employees, 3) To find out and test whether leadership style, organizational culture and motivation partially influence on employee performance, 4) To know which among the leadership style, organizational culture and motivation that dominant influence on employee performance. Based on the results of data analysis found that simultaneous, Leadership style (X1), Organizational culture (X2), Motivation (X3) have a significant effect on the performance of employees of Saronggi District Office of Sumenep Regency, as evidenced by the value of F arithmetic with significance value less than 0.05. And based on the results of data analysis using t test found that leadership style (X1) have a significant effect on employee performance (Y). Similarly organizational culture (X2) and motivation (X3) also have a significant effect on employee performance (Y). Keywords: Style of leadership (X1), Organizational culture (X2), Motivation (X3) And Achievement of employee (Y).